2007
DOI: 10.1590/s0100-879x2007000500005
|View full text |Cite
|
Sign up to set email alerts
|

Sleep deprivation reduces the lymphocyte count in a non-obese mouse model of type 1 diabetes mellitus

Abstract: The objective of the present study was to determine whether sleep deprivation (SD) would promote changes in lymphocyte numbers in a type 1 diabetes model (non-obese diabetic, NOD, mouse strain) and to determine whether SD would affect female and male NOD compared to Swiss mice. The number of lymphocytes in peripheral blood after 24 and 96 h of SD (by multiple platform method) or equivalent period of time in home-cage controls was examined prior to the onset of diabetes. SD for 96 h significantly reduced lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Epidemiological data indicate that sleep deprivation has a mutually conditional relationship, e.g. pain leads to insomnia and sleep deficiency decreases the pain threshold and contributes to the extended periods of wound healing (Mostaghimi et al ., ), to the reduction of growth hormone (Ruiz et al ., ) and to affecting metabolic, endocrine and immunological responses (Spiegel et al ., ). Studies confirm an increased incidence of hypertension, heart rate (Arora et al ., ), the presence of delirium and confusion (Figueroa‐Ramos et al ., ; Patel et al ., ), a decreased performance in daily activities and reduced quality of life, as determined by a questionnaire completed by patients (Martin et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological data indicate that sleep deprivation has a mutually conditional relationship, e.g. pain leads to insomnia and sleep deficiency decreases the pain threshold and contributes to the extended periods of wound healing (Mostaghimi et al ., ), to the reduction of growth hormone (Ruiz et al ., ) and to affecting metabolic, endocrine and immunological responses (Spiegel et al ., ). Studies confirm an increased incidence of hypertension, heart rate (Arora et al ., ), the presence of delirium and confusion (Figueroa‐Ramos et al ., ; Patel et al ., ), a decreased performance in daily activities and reduced quality of life, as determined by a questionnaire completed by patients (Martin et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The primary function of sleep remains unknown, but the fact that prolonged sleep deprivation results in the death of experimental animals indicates that it is essential for survival (Rechtschaffen, ). Reinforcing the importance of sleep, poor sleep quality is associated in humans with an increased risk of developing metabolic syndrome, and in experimental animals with infectious diseases and changes in sexual motivation (Andersen et al, ; Knutson, Spiegel, Penev, & Van Cauter, ; Lungato et al, ; Ruiz, Andersen, Zager, Martins, & Tufik, ). The first two studies linking sleep deprivation to pregnancy loss were published by Pigareva () and by Calegare et al (), both in experimental animals.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have shown that poor sleep increases susceptibility to diseases (1,5,40). Various biochemical studies have demonstrated that sleep loss can alter immune responses in both animals and humans (41)(42)(43). Leukocyte proliferation, humoral immunity, cell-mediated immunity, and immunoglobulin levels are reduced in participants with prolonged sleep disorders (44).…”
Section: Discussionmentioning
confidence: 99%